The Thanksgiving Day from the Black Lagoon - Thaler, Mike, 1936-; Lee, Jared D. (New York : Scholastic, 2009)
Hubie's class is giving thanks for the things they enjoy most, but how can Hubie be thankful when none of his friends will make a float with him? How can Hubie eat all of the food for Thanksgiving dinner?
Reading level: 2.3.
Guided reading level: N.
Lexile: 670L.
Keywords: Thanksgiving Day -- Juvenile fiction; Parade floats -- Juvenile fiction; Monsters -- Juvenile fiction; Parades -- Juvenile fiction; Thanksgiving Day -- Fiction; Parades -- Fiction; Monsters -- Fiction